Unintended Consequences: Does Aid Promote Arms Races? - Collier, P; Hoeffler, A (Blackwell Publishing, 2007)
Using global data for the period 1960-99, we model military expenditure. Neighbours' military spending and development aid are important determinants of military expenditure. An implication of the model is that there are regional arms races which are fuelled by aid. Potentially, aid is encouraging a 'regional public bad'. There may, however, be an offsetting public good effect if military spending deters rebellions. In a simultaneous equation model, we find no deterrence effect of spending on the risk of civil war. Hence, there appears to be no regional public good effect offsetting the public bad arising from a neighbourhood arms race.